18F-FDG PET/CT Follow-up of Rosai-Dorfman Disease. (August 2015) - Albano, Domenico; Bosio, Giovanni; Bertagna, Francesco
Abstract : Abstract: Rosai-Dorfman disease (RDD) or sinus histiocytosis is a rare histiocytic disorder characterized by massive lymphadenopathy and with extranodal involvement in 25% to 43% of cases. The clinical course of RDD is unpredictable with episodes of exacerbation and remissions that can last many years, and treatment strategies can be different according to organ involvement. We report a case of a 42-year-old woman with extranodal disease followed for almost 10 years from the diagnosis who underwent seven 18 F-FDG PET/CT. PET/CT has proven to be a useful method for the management of this patient, mainly for the staging, follow-up, and evaluation of treatment results.